(untitled) - Chipp, Hersche B (Berkeley, Los Angeles, 1968)
The book porvides the basic theories and concepts of modern art. It begins with the masters of Postimpressionism, Cézanne, Van Gogh, and Gauguin, whose ideas are important foundations for later movements. The content of this book is arranged in chronological order, but this system is occasionally modified, as with Gauguin's writings, where certain themes seem important enough to be grouped together. Contemporary artists are listed separately as individuals, in accordance with the nature of their ideas. In all cases the date of writing is considered of primary importance and hence it is always cited when known
Keywords: arts; history